An attempt to assess the efficacy of the new approach to obtaining the diplomas of chartered accountant and auditor in Algeria - zadel, hocine (Journal of Research in Finance and Accounting, 2026)
The present study aims to evaluate the new trend to obtain the diplomas of the accounting expert and the accountant in Algeria, by highlighting the main requirements for the new educational path in accordance with the decisions and executive decrees issued. In order to achieve the objectives of the study, we used a questionnaire designed and distributed to a sample of 82 accountants and auditors. The study concluded that the new approach adopted by Algeria to grant accounting expert diploma and maintain accounts will contribute to raising the efficiency of professionals to include preliminary selection, theoretical training, and vocational training. The study also found shortcomings in the new track and recommended the need to reconsider them, especially with regard to the disciplines that grant the right to participate in the competition, the content of the educational programs at the institute, and some of the practical training procedures.